A systematic evaluation of extensions for the shared customer collaboration vehicle routing problem - Barbara Himstedt; Frank Meisel (Logistics Research, 2021)
This paper takes up a recently published model for collaborative vehicle routing, where shared customers expect shipments from more than one carrier. It is the purpose of the model to decide whether the demands of such a customer are served through individual visits of the involved carriers or through a single visit of one of these carriers. We take up this model and extend it here in three ways. First, a cost restriction is included to make sure that no carrier is worse off in the collaboration solution compared to its isolated route planning. Second, we add time windows that play a major role in service-oriented distribution systems. Third, we include inter-depot freight transfers that are needed if a shared customer receives the goods requested at various carriers through a single visit of one of the carriers. Through our systematic consideration of these three extensions, we can conduct comparative experiments that assess the impact of each such extension on the cost savings that are achieved through the collaboration.
Keywords: 650; carrier collaboration; vehicle routing; shared customers; model extensions